Language Maintenance and Language Shift with Particular Reference to the Spread of English - Tofan Dwi Hardjanto (Humaniora, 1997)
In 1964 Fishman introduced in his study of the languages of the minority immigrants in the US the concepts of language maintenance and language shift (LMLS) as a separate field of inquiry. However, it was only after a number of years later that extensive studies were devoted to the investigatOn of these notions. Various scholars working in the field of lingustics, sociolinguistics,  anthropological linguistics, and even social psychology began to examine from their own perspective points of view these phenomena together with aspects associated with them. Many scholarly attempts have since then flourished to study LMLS not only in developed countries but also- to a varying degree-in developing countries. As a result of these extensive studies, the concepts of LMLS have also undergone development and modification, partly also because of the varied methods employed.